Mekanisme Penerapan Smart Contract pada Joint Venture dalam Penanaman Modal Asing sebagai Inovasi Hukum bagi Ekonomi Hijau Indonesia - Eva Putri, Catharina Crisanty (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital transformation of the global economy has driven the emergence of technology-based legal innovations, one of which is the implementation of smart contracts in Foreign Direct Investment (FDI) activities. This study aims to analyze the mechanism of smart contract implementation within FDI-based joint venture schemes in Indonesia and to assess its role in promoting the green economy. The research employs a normative and conceptual juridical approach by examining legislation, legal doctrines, and practical applications of smart contracts in the investment sector. The findings indicate that smart contracts, as automated electronic agreements based on blockchain technology, are capable of independently executing contractual terms once the agreed conditions are fulfilled. The integration of oracle systems enables real-time verification of administrative, financial, and environmental processes, thereby enhancing efficiency, transparency, and accountability in cross-border investments. The application of smart contracts in FDI joint ventures has the potential to strengthen legal certainty, reduce bureaucratic risks and moral hazards, and promote sustainable investment practices aligned with low-carbon economic principles as mandated by Presidential Regulation No. 98 of 2021 on Carbon Economic Value. Despite its promising potential, the implementation of smart contracts in Indonesia still faces several challenges, including normative gaps, the absence of legal standards governing oracle status, and limited digital infrastructure readiness.